Razvoj izdelave avtomobilov in prevozov v Srednji Evropi v letih 2000 do 2020 - Lešinský, Ján (Strojniški vestnik, 2001)
Materials, energy, the need to reduce losses, technological possibilities, technical solutions, customer requirements car with respect to price, utility properties and safety, all influence the production of cars, their shape, use,and their "return" into a new product. In a steadily increasing way this has enabled designers to use new materials in vehicles, mainly in the last twenty years of the last century. This paper deals with the expected development over the next twenty years from the point of view of the many aspects of vehicle production, globalisation and changes pre-conditioned by the purpose of transport and the means of transportation.
Keywords: mobilnost; izdelava avtomobilov; gostota vozil; porazdelitev; automotive industry; avtomobilska industrija; razvoj; Europe; Evropa